Analysis of the Procedure for Granting Emoluments to Employees in the Environment of PT Kereta Api Indonesia Operational Area 5 Purwokerto - Marcela, Dea; Azizah, Siti Nur; Pratama, Bima Cinintya (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to determine how the emolument procedure is implemented at PT Kereta Api Indonesia Operational Area 5 Purwokerto and its relationship with human resource management policies. Although the emolument structure has been developed based on the principles of accountability and performance, there are still challenges in its implementation, particularly related to the discontinuation of employee diploma equivalence. This has resulted in the non-recognition of educational advancement after appointment as a basis for adjusting rights and remuneration. Additionally, there is an imbalance in the availability of competent human resources, which could potentially affect work effectiveness and service delivery. Primary data was obtained through interviews and direct observation, while secondary data was obtained through literature reviews and relevant documentation. This study highlights the need for a more adaptive reformulation of emolument policies, strategies for human resource equity, and optimization of the civil service information system to achieve fair, efficient, and sustainable human resource management.